Kandungan Total Fungi Serta Jenis Kapang dan Khamir pada Limbah Pabrik Pakan yang Difermentasi dengan Berbagai Aras Starter Starfung - Arinda Kusuma Dewi; Cahya Setya Utama; Sri Mukodiningsih (Agricultural Faculty, 2014)
(Fungis total content, type of molds and yeasts on waste feed mill with various levels of starfung starter)ABSTRACT. This research was conducted to processed the waste feed into a feed mill potentially probiotic functional seen a total of fungi, molds and yeasts and the types of protein biomass increase. The material used in the study were the starter starfung, distilled water and waste feed mill feed. The tools used in the study were an oven, thermometer, drying cabinets, pH meters, moisture meter grand. Research using Rancangan Acak Lengkap (RAL) is 4 treatments with 4 replications. The treatment used T0 = Feed + (Starter 'Starfung' 0%); T1 = Feed + (Starter 'starfung' 1%); T2 = Feed + (Starter 'Starfung' 3%); T3 = Feed + (Starter 'Starfung' 2%). The parameter is were observed total fungi, the type of mold fungi and yeasts. The data total fungi analyzed using analysis of variance and multiple regions continued with Duncan's test to determine differences between treatments. Based on the results of the study showed that the feed mill waste fermentation with starter cedar starfung no significant effect (p 0.05) of total fungi. Average - Average total fungi on treatment T0, T1, T2, and T3 respectively - also is 1,77x107, 1,87x107, 0,9 x107, dan 0,91 x107 Cfu/g. Type of mold is Rhizopus sp and type of yeast is Saccharomyces sp. Conclusion The study is fermented feed mill waste to produce cedar starter starfung Rhizopus sp types and kinds of yeast Saccharomyces sp.